2023
DOI: 10.26811/peuradeun.v11i2.895
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Puzzle Games for Early Childhood Based on the Banten Local Culture

Abstract: Developing a digital puzzle game model is a learning innovation for early childhood cognitive development. The current research purpose was to develop a digital games puzzle based on Banten culture for early childhood; The method applied was the research and development of ADDIE's model with the 30 children as samples. The results revealed five puzzle game objects and levels 1-3. The weakness of this puzzle game was that there was no animation, while the advantages of this puzzle game were that it was easy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Actions that are considered approaching adultery include all forms of speech, attitudes, thoughts, and actions that can trigger sexual instincts and can lead to the occurrence of adultery (Asmawati, 2023;Thamrin, Ghasya, & Pranata, 2023). For elementary school-age children, they are not subject to the law in this verse because they have not reached puberty.…”
Section: Non Co-educationmentioning
confidence: 99%
“…Actions that are considered approaching adultery include all forms of speech, attitudes, thoughts, and actions that can trigger sexual instincts and can lead to the occurrence of adultery (Asmawati, 2023;Thamrin, Ghasya, & Pranata, 2023). For elementary school-age children, they are not subject to the law in this verse because they have not reached puberty.…”
Section: Non Co-educationmentioning
confidence: 99%
“…Teori ini mengarahkan perhatian pada peran krusial pengalaman langsung dalam mengembangkan pemahaman yang mendalam dan berkelanjutan. Melalui penggunaan barang bekas, siswa tidak hanya diperkenalkan pada konsep matematika secara abstrak, tetapi mereka juga diberikan kesempatan untuk berinteraksi dengan konsep tersebut dalam konteks dunia nyata (Asmawati, 2023).…”
Section: Pembahasanunclassified
“…In Indonesia, research and development of digital puzzles for children are increasingly being carried out, particularly before and after the COVID-19 pandemic (Kristianti et al, 2018;Maududi et al, 2018;Widyatmoko, 2019;Wathoni et al, 2021;Rizkiyah et al, 2022;Asmawati, 2023;Ramlah Abadi et al, 2023). Based on several of this research, we focused on research and development of digital puzzles to develop resilience in the context of early childhood education.…”
Section: Digital Puzzles For Resilience: the Case Of Early Childhood ...mentioning
confidence: 99%
“…Recently, Asmawati (2023) developed a digital puzzle based on the local wisdom of Banten culture. She found that digital puzzles improved the cognitive development of young children.…”
Section: Digital Puzzles For Resilience: the Case Of Early Childhood ...mentioning
confidence: 99%